2012
DOI: 10.5430/jnep.v3n2p41
|View full text |Cite
|
Sign up to set email alerts
|

Mentorship provision for student nurses: Conceptions of Finnish and British mentors in healthcare placements

Abstract: Background: The unification process for clinical education in Europe seeks to standardise the attainment of competencies by students and effective mentorship is central to this.Aim: This paper is a report on a study describing Finnish and British mentors' conceptions of mentorship provision for pre-registration nursing students during placement learning in healthcare settings. Methods:This qualitative study adopted a phenomenographical approach, which focused on the different ways mentorship provision for stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
7
0
3
Order By: Relevance
“…Mentoring is a key element of students´ clinical learning, and hence nursing education (Tuomikoski et al, 2018b). Thus, improving mentors´ competences in clinical settings enhances nursing students´ competences and their professional identity (Jokelainen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mentoring is a key element of students´ clinical learning, and hence nursing education (Tuomikoski et al, 2018b). Thus, improving mentors´ competences in clinical settings enhances nursing students´ competences and their professional identity (Jokelainen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Antohe et al (2016) state that supervision and mentoring are supportive relationships, which help individuals to obtain new skill, knowledge and approaches. Students mentorships require qualified and experienced nurses to act as mentors for individual students (Jokelainen et al, 2013). The study results revealed statistically significant differences between the attitude of the students supervised by ward manager and students supervised by registered nurse.…”
Section: Discussionmentioning
confidence: 87%
“…Mentors are also expected to facilitate a supportive learning environment and conduct an assessment on the student's performance and attainment of clinical skills (Ali & etc., 2008). This role requires mentors to facilitate students' personal and professional growth and the development of nursing competencies (Jokelainen et al, 2013). It has been presented that a mentor acts as a role model, and guides and advises a student (Myall et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Aukštojo mokslo institucijos, remiantis Europos Sąjungos direktyvomis, vykdo slaugos studijų programas, kurios užtikrina kompetencijų, būtinų profesinei slaugos praktikai, įgijimą (Jokelainen, Jamookeeah, Tossavainen, Turunen, 2013). Slauga yra ir menas, ir mokslas, reikalaujantis specifinių slaugos žinių, gebėjimų taikymo praktinėje veikloje.…”
Section: įVadasunclassified